About one way of organization Unified system for registration of space rays - Mukashev, K.M.; Stepanov, A.V.; Argynova, A.Kh.; Zhukov, V.V.; Idrisova, T.K. (KU Publ., 2021)
Today, at the high-mountain scientific station for the study of the physics of cosmic rays, various, independently operating unique experimental installations are used. The ways and methods of combining these installations into a single system are discussed in the article. A single system includes networks of scintillation detectors of the "carpet" type for registration of the electron-photon component, ground and underground monitors for registration of neutron components, calorimeters, Cherenkov detectors, a scintillation spectrometer and a number of other subsystems. The newly created unified system for registering cosmic rays based on the achievements of modern technology and scientific thought will have a high resolution, with a common databank with synchronization in time of operation of separate, independently operating experimental installations. The solution to this problem will help to perform a detailed analysis of the recorded events from a single position, to carry out complex calculations of the spatial distribution, mass composition, and also the energy structure of cosmic rays with a high degree of accuracy. Significant scientific results, obtained in recent years at the Horizon-T experimental installation, are provided. The presented preliminary significant data obtained during the implementation of the project testify to the high information content of the obtained results.
Ғарыш сəулесін тіркеуге арналған бірегей жүйені құрудың бір тəсілі туралы
Об одном способе организации единой системы регистрации космических лучей
Keywords: cosmic rays; scintillation detector; neutron monitors; fiber optics; local area network; server; extensive air showers; unified database